Catastrophic thinking and functional disability in Primary Health Care chronic pain patients - Lins,José Jefferson da Silva Cavalcanti (2021)
ABSTRACT BACKGROUND AND OBJECTIVES: Catastrophic thoughts are an important evaluative factor because they interfere with pain management and degree of disability since they affect responses to pain. The study aimed to investigate the relationship between catastrophic thoughts and the dimensions of functional disability in patients with chronic musculoskeletal pain in primary health care. METHODS: A cross-sectional descriptive study that included 50 patients of both genders, aged 18 to 59 years, with chronic musculoskeletal pain, with intensity from 3 to 7 by the visual analog scale. To evaluate pain catastrophization, the Brazil validated Pain Catastrophizing Scale (B-PCS) was used and the interference of pain on function was assessed by the Pain Disability Index (PDI). RESULTS: The majority of patients were female (94%), mean age 42±10.3 years, median pain 7 [6-7], basic schooling level (62%), unemployed (66%), and sedentary (76%). Catastrophizing (56%). The regions with the highest prevalence of pain were thoracolumbar (38%), anterior knees (32%), lumbosacral and face (30%). There was a direct and significant correlation between the PCS and PDI scores (ρ=0.56; p<0.01), as well as between the PDI scores and the subdomains: rumination (ρ=0.34; p <0.01), magnification (ρ=0.57; p <0.01) and helplessness (ρ=0.53; p <0.01). CONCLUSION: People with chronic pain demonstrate a tendency towards the most unpleasant aspects of pain, resulting in less participation in daily activities, with impacts on functional capacity.